Analisis Pengaruh Model Pembelajaran Discovery Learning dengan Pendekatan Deep Learning Terhadap Kemampuan Pemahaman Konsep dan Penalaran Matematis Siswa Pada Materi SPLTV - manalu, vriti sinta; Simanjuntak, Ruth Mayasari; Sihombing, Dame Ifa (Universitas PGRI Semarang, 2026)
This study aims to analyze the effect of the Discovery Learning model with a Deep Learning approach on students' conceptual understanding and mathematical reasoning abilities on the topic of Three Variable Linear Equation Systems (SPLTV) in grade X of SMA Negeri 17 Medan in the 2025/2026 academic year. This study used a quantitative approach with a quasi-experimental design. The sample consisted of class X-4 as the experimental class and class X-6 as the control class selected through cluster random sampling. Data were collected using tests, questionnaires, and observation sheets. The data were analyzed using descriptive and inferential analysis. The results showed that the Discovery Learning model with a Deep Learning approach had a significant effect on students' conceptual understanding and mathematical reasoning abilities with a significance value 0.05. In addition, students taught using this model showed better conceptual understanding than those taught using conventional learning. The implementation of this model also increased students' active participation in mathematics learning.